A case report of reattachment of fractured root fragment and resin-composite reinforcement in a compromised endodontically treated root - Lui, J.L. (2001)
The composite reinforcement technique has been used clinically to salvage damaged root-filled teeth compromised by caries, trauma, developmental abnormalities, internal resorption and iatrogenic causes. This clinical case report describes the use of the technique to reattach a fractured fragment in a compromised endodontically treated root besides reinforcing it for continued function in the mouth. Factors of clinical importance related to this additional application; including reattachment of tooth fragments, post crown retention, coronal microleakage and fracture resistance and strength, are also briefly discussed.